Integrated water and nutrient management in Sathgudi sweet orange (Citrus sinensis) - LAKASHMI, L MUKUNDA; VENKATARAMANA, K T; SHIRGURE, P S; SRIVASTAVA, A K; PATIL, PRAKASH (The Indian Journal of Agricultural Sciences, 2019)
The combined effect of drip irrigation with fertigation on plant growth, yield and quality of 10 year-old bearing sweet orange (Citrus sinensis cv. Sathgudi) was studied during 2013–17 at Dr YSR Horticultural University, AICRP on Fruits, CRS, Tirupati. The experiment was laid out in factorial randomised block design with nine treatment combinations, comprising three irrigation schedules, viz. 70 % evaporation replenishment (ER) , 80 % ER , and 90 % ER , and three fertigation levels, viz. fertigation with 60 % RDF (recommended dose of fertilizers), 70% RDF and 80% RDF based NPK doses replicated six times. The maximum plant canopy volume (16.84 m3), fruit yield (14.18 t/ha) and TSS/acidity ratio (20.7) of sweet orange was observed with the drip irrigation scheduled at 90 % ER combined with 70 % RDF fertigation treatment combination. The fruit yield efficiency per unit of canopy volume was also observed maximum (0.84) with irrigation scheduling at 90 % ER and fertigation with 70 % RDF dose. The sustainable production of sweet orange was obtained with irrigation scheduling at 90 % ER along with fertigation technology at 70 % RDF with 27-30% saving in water and fertilizers.